2022
DOI: 10.26466/opusjsr.1098233
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Algılarına Göre Okul Müdürlerinin Eleştirel Liderlik Davranışlarının Okul İklimine Etkisi

Abstract: The aim of the study is to determine whether school principals' critical leadership behaviors have an effect on the school climate. For this purpose, data were collected from 836 teachers working in different types of public schools in the province of Istanbul, using the relational survey model, by using the easily accessible sampling method. For the analysis of the data obtained through Demographic Information Form, Critical Leadership Scale and School Climate Scale, SPSS 22.0 package program was used. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Gender was claimed to cause a significant difference in the perception of paternalistic leadership in some studies (Cerit et al, 2011;Delice, 2020;Dursun, 2019;Kara et al, 2020;Karşu Cesur, 2015;Kılıç, 2019;Mert & Özgenel, 2020;Özgenel & Dursun, 2020;Saylık, 2017), while it was claimed not to cause a significant difference in some other studies (Ağalday, 2017;Arslan, 2016;Aydınoğlu, 2020;Bilici, 2017;Burgazlıoğlu, 2022;Dağlı & Ağalday, 2018;Hatipoğlu et al, 2019;İncegöz & Uslu, 2022;Koç, 2019;Korkmaz, 2018;Nal, 2018;Özgenel & Canuylası, 2021;Sarı, 2021). However, while it was revealed in only one research that the paternalistic leadership perception of female participants was higher than that of male participants (Kara et al, 2020), other studies asserted that the paternalistic leadership perception of male participants was higher than that of female participants in general (Cerit et al, 2011;Delice, 2020;Dursun, 2019;Karşu Cesur, 2015;Kılınç, 2019;Mert & Özgenel, 2020;Özgenel & Dursun, 2020;Saylık, 2017). In almost all of the research carried out with samples from Türkiye, gender does not have a significant effect on the perception of paternalistic leadership, and men have higher perceptions of paternalistic leadership than that of women, and these might be related to Türkiye's male-dominated social dynamics and cultural values with collectivist characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender was claimed to cause a significant difference in the perception of paternalistic leadership in some studies (Cerit et al, 2011;Delice, 2020;Dursun, 2019;Kara et al, 2020;Karşu Cesur, 2015;Kılıç, 2019;Mert & Özgenel, 2020;Özgenel & Dursun, 2020;Saylık, 2017), while it was claimed not to cause a significant difference in some other studies (Ağalday, 2017;Arslan, 2016;Aydınoğlu, 2020;Bilici, 2017;Burgazlıoğlu, 2022;Dağlı & Ağalday, 2018;Hatipoğlu et al, 2019;İncegöz & Uslu, 2022;Koç, 2019;Korkmaz, 2018;Nal, 2018;Özgenel & Canuylası, 2021;Sarı, 2021). However, while it was revealed in only one research that the paternalistic leadership perception of female participants was higher than that of male participants (Kara et al, 2020), other studies asserted that the paternalistic leadership perception of male participants was higher than that of female participants in general (Cerit et al, 2011;Delice, 2020;Dursun, 2019;Karşu Cesur, 2015;Kılınç, 2019;Mert & Özgenel, 2020;Özgenel & Dursun, 2020;Saylık, 2017). In almost all of the research carried out with samples from Türkiye, gender does not have a significant effect on the perception of paternalistic leadership, and men have higher perceptions of paternalistic leadership than that of women, and these might be related to Türkiye's male-dominated social dynamics and cultural values with collectivist characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, research examining the perception of paternalistic leadership in Türkiye according to demographic variables such as gender and marital status is remarkable. Some of the research revealed that gender causes a significant difference on the perception of paternalistic leadership (Cerit et al, 2011;Delice, 2020;Dursun, 2019;Kara et al, 2020;Karşu Cesur, 2015;Kılınç, 2019;Mert & Özgenel, 2020;Özgenel & Dursun, 2020;Saylık, 2017), while some advocated that it does not cause a significant difference (Ağalday, 2017;Arslan, 2016;Aydınoğlu, 2020;Bilici, 2017;Burgazlıoğlu, 2022;Dağlı & Ağalday, 2018;Hatipoğlu et al, 2019;İncegöz & Uslu, 2022;Koç, 2019;Korkmaz, 2018;Nal, 2018;Özgenel & Canulansı, 2021;Sarı, 2021). Concerning the marital status variable, some research pointed to a significant difference in the perception of paternalistic leadership (Abacı, 2020;Taşdemir & Atalmış, 2021), while some advocated that there is no significant difference (Ağalday, 2017;Aydınoğlu, 2020;Burgazlıoğlu, 2022;Korkmaz, 2018;Sarı, 2021;Saylık, 2017;Dağlı & Ağalday, 2018;Delice, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It shows that school heads professional standards serve as a public statement of professional responsibility of school heads. Dursun et al (2022) stated that the manner in which the principals carry out a task, as well as their attitudes, actions, and abilities, are the major variables impacting the climate type of the business. Additionally, the leadership style of a company's leaders has an impact.…”
Section: Theoretical Frameworkmentioning
confidence: 99%